The Role Of Police Investigators In Overcoming Motor Vehicle Theft (Curanmor) In Police Area Pakpak Bharat Resort - Widodo Kaban (Journal of Law Science, 2022)
The increase in cases of motor vehicle theft cannot be avoided due to the increasing growth rate of motorized vehicles which is quite high in the Pakpak Bharat Resort Police (Polres). The Ministry of Transportation said that the growth rate of motorized vehicles was very disproportionate to the length of the existing road, that the length of the road was no longer able to accommodate the volume of motorized vehicles. The problems posed are: what is the form of the act of motor vehicle theft in Pakpak Bharat, what is the role of the police in motor vehicle theft in Pakpak Bharat and what are the obstacles and efforts faced by the police in overcoming motor vehicle theft. The results of the research and discussion explain that the forms of theft of motorized vehicles in Pakpak Bharat are carried out in various ways, namely: using fake keys, damaging motorized ignition keys, damaging four-wheeled motorized vehicle doors, pointing with firearms and pointing with sharp weapons as well as depriving and take by force by injuring the victim. The role of the National Police in motor vehicle theft in Pakpak Bharat is to conduct investigations and take action on public reports of motor vehicle theft, with details of the main tasks as follows: as law enforcers, as protectors and as community guides. Efforts that can be made by the police in overcoming motor vehicle theft are by conducting raids and patrols in places that are suspected of being prone to motor vehicle theft and socialization about the use of additional keys. The obstacle faced by the police in overcoming the theft of motor vehicles is the difficulty in identifying the perpetrators of the theft. Motor vehicle theft is currently experiencing growth and development with neat characteristics, has a kind of bureaucracy of its own, is resistant to social reactions and is able to spread a network of activities in such a way that it has a wide scope coupled with a high quality to avoid law enforcement efforts through various means.